Estructura y caracterización dasométrica del arbolado en las parroquias Urbanas del Cantón Quevedo. - Moreira García, Mayra Katherine (2017)
The objective of the research was to determine the structure and characterization of the tree in the urban parishes of Quevedo, in the province of Los Ríos, Ecuador. The study was carried out in the nine urban parishes, which were inventoried by sectors, finding 43 green areas and 9 arboreal beds. For the analysis of the structure were applied the dasometric variables as common name, diameter, total height density and basal area ratio - canopy cover. In the analysis of species diversity, frequency parameters, Shannon-Wiener (H ') and Simpson (D) diversity indexes were taken into account. In the classification of green areas the parish Quevedo presented an average value of 11 green areas. In the number of individuals the parish San Camilo indicated an average of 463 individuals. The parish of Siete de Octubre presented the largest cup diameter with an average of 4.48 m. The most representative total height was presented by the Guayacan parish with an average of 4.97 m. The largest volume of wood was found in the parish of San Camilo with an average of 84.99 m3. The Quevedo parish presented an average density of trees per hectare of 3.21. . The absolute frequency analysis determined that the species with the highest frequency were Adonidia merrillii (Becc.) Becc., Ficus benjamina L, Phoenix roebelenii O'Brien. The Shannon Index determined that parish May 24 had an average value of 3,076. The Simpson Index indicated that the parish 24 de Mayo had an average value of 0.933. The linear correlation analysis indicated that the highest value was presented by the Nicolás Infante Díaz parish with a coefficient of determination of R2 = 901 and a linear regression equation y = -19,419 x + 6,335The largest number of species was presented in the Quevedo parish with An average value of 42 species.